INFLUENCE OF TECHNOLOGY AND IT’S IMPACT ON URBAN MIGRATION PRODUCTIVE CAPACITY - Ramakrishnan, Dr. Hemalatha; Sahoo, Dr. Niranjan; Jalem, Dr Kiran; M Nayak, Dr. Keyur kumar; Ramanathan, Dr. Vanisree; Dr. M. Christopher (The journal of contemporary issues in business and government, 2022)
Innovative technology creates new ways that have developed integrity and complexity. In the current scenario with active drive, the Fourth Industrial Revolution builds on the Digital Revolution, representing new ways in which technology becomes embedded in decision making. With new waves, sustainable economic development needs to be relooked. Where does India stand, in its development of human capital? Has skill development grown with technology, if not, is there any scares to Indian sustainable growth with human capital. Technology and globalization are significantly changing work. Has technology boosted productivity? Should Techeconomics use information economics blend for productive sustainable goals? To investigate these issues firstly, stages in the technology revolution is looked upon to recall shocks. Trends in urban population, migration stock, is analyzed and thirdly, technology facilitators, labor force, devices, and broadband subscriptions are analyzed. Also, India’s export of services relating to information and communication is taken into account. Does theory indicate technology has expanded production capacity, however, traditional economic theory and law do they hold relevance today with static technology assumption? Various production laws have developed theory assumptions with absolute static technology. With progress in technology. Indian urban population, in its, technology innovation has acknowledged as passive adapters and an attempt to find and explore innovation is of little attempt. The paper would like to find, if there are very few able-bodied minds that have impacted productive capacity while rest are passive adapters. Penetration has raised scope for the export market, rather a perception is sliding due to indifference and trade-off mindset of the labor force.